Synergistic electronic and geometric effects of Au/CeO2 catalyst for oxidative esterification of methacrolein. Issue 1 (31st October 2022) - Farooq, Muhammad U.; Zhang, Xiangxue; Guan, Yanan; Chen, Wenyao; Zhou, Jinghong; Zhang, Jing; Qian, Gang; Duan, Xuezhi; Zhou, Xinggui; Yuan, Weikang
Abstract: Methyl methacrylate (MMA) is an important monomer for the production of acrylic plastics and polymer dispersions. In this study, we demonstrate a strategy to synergize the electronic and geometric effects of the Au/CeO2 catalyst, achieving three orders of magnitude improvement in reaction rate for the oxidative esterification of methacrolein to MMA. The electronic properties of Au in terms of the valence electron population of 5d states are decoupled from the redox ability and acid–base properties of catalyst support as the main cause for the significant increase in the specific activity of the active site. Moreover, the Au edge site is identified as the main active site for this reaction, whose number reaches the maximum for the 1.6 nm‐sized Au particles. Hence, the synergism between the electronic (lower valence electron population of 5d states) and geometric (more edge active sites) promotions of the Au‐10/CeO2 catalyst contributes to the highest catalytic activity.